Small ruminant production in coffee-based mixed crop-livestock system of Western Ethiopian Highlands: Status and prospectus for improvement - Shenkute, S.; Legasse, G.; Tegegne, Azage; Hassen, A. (2010)
The study was conducted in Goma district of Jimma Zone of Ethiopia with the objectives of documenting the reasons why farmers in coffee dominant mixed-farming systems of western Ethiopia keep small ruminants, and identifying the constraints and opportunities for improvement of this sector. Results are based on diagnostic survey of 160 sample households, group discussions and personal observation. The study district was stratified into three groups based on flock distribution as: sheep dominating, goat dominating and mixed flock sites. The average land holding per household was 1.93 ha. In Goma where coffee and chat are the major cash sources for farmers, small ruminant are also primarily kept for cash generation as reported by 94% of the sampled households. The second main reason for keeping small ruminant in the study area was for saving mainly in time of coffee failure. Keeping small ruminants as a source of manure was the third important reason. From the interviewed households, 59.4, 32.1, 23.5, and 19.4% of them utilize communal grazing, aftermath grazing, roadside grazing, and riverside grazing, respectively for their animal as a sources of feed. Most small ruminants are either tethered or herded all the seasons due to the cultivation of perennial crops and predators. All small ruminants are housed for protection from adverse weather conditions and predators. The major problems for small ruminant production and marketing were: feed and grazing land shortage, lack of input, predators, diseases and parasites and marketing problems. In order to exploit the current growing demand of small ruminant meat at local and international markets, research and development interventions are required with regard to the identification of alternative feed resources and strategic feeding management, identification of causes of diseases and their control methods and improving marketing efficiency through appropriate policy.